Current management and future directions in metastatic pancreatic adenocarcinoma - Varghese, Anna M.; Lowery, Maeve A.; Yu, Kenneth H.; O'Reilly, Eileen M. (Cancer, 2016)
Of the anticipated 50,000 individuals expected to be diagnosed with pancreatic cancer in 2016, the majority will have metastatic disease. Given the noncurative nature of advanced pancreatic adenocarcinoma, treatment is aimed at inducing disease regression, controlling symptom, and extending life. The last 5 years have been marked by advances in the treatment of metastatic pancreatic cancer, specifically the approval by the US Food and Drug Administration of 2 combination chemotherapy regimens and the widespread use of a third, which have reproducibly been shown to improve survival. Ongoing studies are building on these regimens along with targeted and immunotherapeutic agents. This article will review the current treatment standards and emerging targets for metastatic pancreatic cancer. Cancer 2016;122:3765–3775. © 2016 American Cancer Society. The management of patients with metastatic pancreatic cancer has evolved within the last 5 years due to the approval of several new combination regimens. A growing understanding of the complex roles and interplay of the immune system, tumor stroma, and molecular biology of this disease has poised the field for meaningful change in the proximate future.